De maagd van Orléans - Fabre, Lucien, 1889-1952; Gescher, B. (Utrecht : Spectrum, 1955)
Domrémy - Vancouleurs - Chinon - Orléans - Reims - Compiègne - Rouaan - Cauchon - Parijs - Rome
Keywords: Jeanne d'Arc, -- 1412-1431.